(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
An apparatus that moves heat from one fluid to another is a heat exchanger. To avoid mixing, the fluids may be separated by a solid wall, or they may be in direct touchHairpin Exchangers are available in bare tubes, finned tubes, U-tubes, straight tubes (with rod-thru capability), fixed tube sheets, and detachable bundles. They also come in single tubes (Double Pipe) and numerous tubes within a hairpin shell (Multitude). The combination characteristics of nano fluid and base fluid water are calculated in this article. Magnesium Oxide and silver nano particle volume fractions of 0.35, 0.45, 0.55, and 0.65 percent at varied velocities (0.5, 1,1.5, and 2 m/s) were used as nano fluids. The properties of nanofluids are calculated theoretically, and the results are used as inputs for analysisA 3D model of the hair pin heat exchanger with and without twisted tape is made using CREO parametric software. CFD analysis of the hair pin heat exchanger is performed at different nanofluid volume fractions. The pressure drop, Reynolds number, heat transfer coefficient, and Nusselt number are all determined using CFD analysis.